Church-Led Social Capital and Public-Health Approaches to Youth Violence in Urban Zimbabwe: Perspectives from Church Leaders - Ndlovu, James (Social sciences (Basel), 2025)
Youth violence in Zimbabwe’s high-density suburbs has evolved into a severe public-health emergency, entrenching trauma, fuelling substance abuse, and amplifying structural inequities. Christian churches remain the most pervasive civic institutions in these settings, commanding high moral authority, psychosocial reach, and convening power. However, the mechanisms by which churches mitigate violence, and the constraints they face, continue to be under-researched. Grounded in socio-economic model lens and faith-based social capital theory, this study interrogates the intersections between youth violence and church responses in Zimbabwe’s urban centres. The study adopts a qualitative approach using semi-structured interviews with church leaders. Twenty (20) church leaders from mainline, Pentecostal, and Apostolic traditions were recruited through purposive and snowball sampling to capture denominational diversity and varying levels of programme engagement. Interviews probed leaders’ perceptions of youth-violence drivers, theological framings of non-violence, practical interventions (e.g., trauma-healing liturgies, anti-drug ministries, peer-mentorship schemes), and institutional constraints such as resource scarcity and political pressures. Data was analysed using reflexive thematic analysis. The findings indicate three interconnected mechanisms through which churches mitigate the cycle of violence. Nevertheless, gendered participation gaps, theological ambivalence toward activism, and limited alignment with municipal safety strategies continue to pose challenges to these efforts. By positioning churches within Zimbabwe’s broader violence-prevention ecology, the study offers an empirically grounded blueprint for integrating faith actors into city-level public-health strategies and contributes towards evidence-based, structural solutions to urban youth violence.